A Tubular DNA Nanodevice as a siRNA/Chemo‐Drug Co‐delivery Vehicle for Combined Cancer Therapy. Issue 5 (1st December 2020) - Wang, Zhaoran; Song, Linlin; Liu, Qing; Tian, Run; Shang, Yingxu; Liu, Fengsong; Liu, Shaoli; Zhao, Shuai; Han, Zihong; Sun, Jiashu; Jiang, Qiao; Ding, Baoquan
Abstract: Using the DNA origami technique, we constructed a DNA nanodevice functionalized with small interfering RNA (siRNA) within its inner cavity and the chemotherapeutic drug doxorubicin (DOX), intercalated in the DNA duplexes. The incorporation of disulfide bonds allows the triggered mechanical opening and release of siRNA in response to intracellular glutathione (GSH) in tumors to knockdown genes key to cancer progression. Combining RNA interference and chemotherapy, the nanodevice induced potent cytotoxicity and tumor growth inhibition, without observable systematic toxicity. Given its autonomous behavior, exceptional designability, potent antitumor activity and marked biocompatibility, this DNA nanodevice represents a promising strategy for precise drug design for cancer therapy. Abstract : An autonomous tubular DNA nanodevice is constructed to deliver a chemotherapeutic drug and siRNAs. This nanodevice can realize on‐demand targeting, respond to stimuli in the intracellular environment and release multiple molecular payloads for combined antitumor activity.